3‐Cyano Imidazopyridine Acceptor‐based Bipolar and n‐type Host Materials for Phosphorescent Organic Light‐Emitting Diodes. Issue 11 (14th August 2018) - Kothavale, Shantaram; Lee, Kyung Hyung; Lee, Jun Yeob
Abstract: Two host materials named 8‐(3‐(9H‐carbazol‐9‐yl)phenyl)‐2‐phenylimidazo[1, 2‐a]pyridine‐3‐carbonitrile (mCzImPy) and 8, 8′‐(1, 3‐phenylene)bis(2‐phenylimidazo[1, 2‐a]pyridine‐3‐carbonitrile) (mBisImPy) were synthesized as a bipolar host and a n‐type host, respectively, from the herocyclic imidazopyridine unit through its 3‐position CN modification. They worked as the hosts of yellow phosphorescent emitter and the mCzImPy host achieved high quantum efficiency of 18.2% in the yellow phosphorescent devices. Therefore, the 3‐cyanoimidazopyridine showed potential as an electron transport unit of host design. Abstract : Two novel CN‐substituted imidazopyridine acceptor based host materials namelymCzImPy andmBisImPy were synthesized as bipolar and n‐type host materials for yellow phosphorescent emitter PO‐01 respectively. Bipolar type host materialmCzImPy achieved high quantum efficiency (18.2%) than n‐type host materialmBisImPy (12.8%). The bipolar designmCzImPy was superior to balance carriers than n‐type molecular designmBisImPy, which is hindering hole transport in the emitting layer.